Performance-Based Budget Implementation in Improving Local Government Performance in Datuk Bandar, Tanjung Balai - Anggi Pratama Nasution (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Performance-Based Budgeting can be interpreted as a form of budget whose sources are linked to the results of government-level services. The budget itself is structured on a performance-oriented approach to output. The budget cycle is the period or timeframe from when the budget is drafted up to the time law passes the calculation of the budget. The budget cycle consists of several stages, preparation, ratification, implementation and evaluation reporting. This research was conducted at all offices in Datuk Bandar Subdistrict, Tanjung Balai City. The purpose of this study is to find out how the implementation of Performance Based Budget in improving the performance of local government with case studies in Datuk subdistrict Bandar Kota Tanjung Balai. Data were taken using questionnaires on those obtained from Budget Authorities and Treasurer at five urban villages and one subdistrict. This data is processed by using the descriptive-analytic method with the qualitative approach. The results of this study indicate that all performance-based budget activities that include planning, implementation, reporting and evaluation as a form of performance improvement at all agencies in Datuk Bandar, Tanjung Balai has been in accordance or running well.